Techniques to infer admixture using genome-wide autosomal DNA 1 - Hellenthal, Garrett (Henry Stewart Talks, 2022)
Introduction and illustrative simulations, ADMIXTURE clustering software, f3-statistics admixture detection software, Autosomal DNA is used to date admixture, ALDER/MALDER admixture detection and dating software